Faktor-Faktor Usaha Tani Kopi di Desa Bolokan Lembang Tiroan Kecamatan Bittuang Kabupaten Tana Toraja - Anisa Alda Belo; Xaverius Erick Lobja; Kalvin Salindeho Andaria (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2022)
The cultivation of coffee plants is closely related to many problems. These challenges are discussed from non-physical and physical aspects in this study, including farmer expertise, land area, capital, and income, as well as physical characteristics based on climate, soil conditions, and terrain. This study uses a qualitative descriptive method. Data was obtained by interviewing informants, taking notes, and collecting secondary information on topography, rainfall, soil type, temperature, and altitude. The findings show that physical and non-physical factors, as well as skills, land area, capital, and income, have a significant impact on coffee growth. These physical elements include topography, soil, and climate. Farmer productivity is affected by the small size of the cultivated land.